ADF, NDF AND HEMICELLULOSA DIGESBILITY IN VITRO IN FERMENTATION LITTERS WITH DIFFERENT RIPENING PERIODS - Cahya Setya Utama; Marry Christiyanto (Jurnal Ilmu Ternak, 2021)
The study aims to examine the length of chicken litter peram against digestibility Acid Detergent Fiber (ADF), digestibility Neutral Detergent Fiber (NDF) and digestibility hemicellulose in vitro.The research method was conducted by collecting chicken litter from 16 closed house cages, combined and fermented. The study used a Complete Randomized Design pattern in the direction of 4 treatments and 4 replays, the treatment is T0 = littering 0 weeks; T1 = 3 weeks litter ripening; T2 = 6 weeks litter ripening; T3 = 9 weeks litter ripening. The observed parameters are ADF digestbility, NDF digestibility and hemicellulose litter of fermented chickens using Van Soest method. The results showed that the long litter of fermented chickens had an effect on the digestiability value of ADF, NDF digestibility and hemicellulose digestibility. Litter treatment of fermented chickens by ripening increases the digestiability of ADF and hemicellulose litter of chickens while the digestitude of NDF treatment is lower than the treatment without acidification. The conclusion of the study was litter of fermented chickens with a length of 6 weeks, resulting in ADF digestibility of 54.15%, digestibility of NDF by 57.20% and digestibility of hemicellulose by 14.35%.